Mass loss rate determinations of southern OB stars - Benaglia, Paula (2001)
A sample of OB stars (eleven Of, one O and one B supergiant) has been surveyed with the Australia Telescope Compact Array at 4.8 and 8.64 GHz with a resolution of ∼2"–4". Five stars were detected; three of them have negative spectral indices, consistent with non-thermal emission, and two have positive indices. The thermal radiation from HD 150135 and HD 163181 can be explained as coming from an optically thick ionized stellar wind. The non-thermal radiation from CD–47◦ 4551, HD 124314 and HD 150136 possibly comes from strong shocks in the wind itself and/or in the wind colliding region if the stars have a massive early-type companion. The percentage of non-thermal emitters among detected O stars has increased up to ∼50%. The Of star HD 124314 clearly shows flux density variations. Mass loss rates (or upper limits) were derived for all the observed stars and the results compared with non-radio measurements and theoretical predictions.